Autosomal recessive transmission of a rare KRT74 variant causes hair and nail ectodermal dysplasia: allelism with dominant woolly hair/hypotrichosis. - Doroteya Raykova; Joakim Klar; Aysha Azhar; Tahir Naeem Khan; Naveed Altaf Malik; Muhammad Iqbal; Muhammad Tariq; Shahid Mahmood Baig; Niklas Dahl (PLoS ONE)
Pure hair and nail ectodermal dysplasia (PHNED) comprises a heterogeneous group of rare heritable disorders characterized by brittle hair, hypotrichosis, onychodystrophy and micronychia. Autosomal recessive (AR) PHNED has previously been associated with mutations in either KRT85 or HOXC13 on chromosome 12p11.1-q14.3. We investigated a consanguineous Pakistani family with AR PHNED linked to the keratin gene cluster on 12p11.1 but without detectable mutations in KRT85 and HOXC13. Whole exome sequencing of affected individuals revealed homozygosity for a rare c.821T>C variant (p.Phe274Ser) in the KRT74 gene that segregates AR PHNED in the family. The transition alters the highly conserved Phe274 residue in the coil 1B domain required for long-range dimerization of keratins, suggesting that the mutation compromises the stability of intermediate filaments. Immunohistochemical (IHC) analyses confirmed a strong keratin-74 expression in the nail matrix, the nail bed and the hyponychium of mouse distal digits, as well as in normal human hair follicles. Furthermore, hair follicles and epidermis of an affected family member stained negative for Keratin-74 suggesting a loss of function mechanism mediated by the Phe274Ser substitution. Our observations show for the first time that homozygosity for a KRT74 missense variant may be associated with AR PHNED. Heterozygous KRT74 mutations have previously been associated with autosomal dominant woolly hair/hypotrichosis simplex (ADWH). Thus, our findings expand the phenotypic spectrum associated with KRT74 mutations and imply that a subtype of AR PHNED is allelic with ADWH.